002 A review of the performance of referring centres in diagnosing sCJD on MRI. Issue 6 (27th May 2022) - Sequeira, Danielle; Jesuthasan, Aaron; Hyare, Harpreet; Odd, Hans; Rudge, Peter; Mok, Tze How; Nihat, Akin; Collinge, John; Mead, Simon
Abstract : Introduction: MRI sensitivity of up to 96% for pre-mortem diagnosis of sporadic Creutzfeldt-Jakob disease (sCJD) has previously been reported. However, in 2012, Carswell et al. found that the initial neuroradio- logical report often failed to identify CJD-associated MRI changes (47% sensitivity). These patients were at a more advanced stage of disease when referred to specialist services. Here we assessed whether there has been a change over time. Methods: We reviewed MRI scans of 106 patients (sCJD=102, IPD=4) referred to the NPC between 2015- 2019, and compared our findings with the formal reports from referring centres. We recorded the MRC Scale scores at initial patient assessment. Results: We found characteristic MRI abnormalities in 101 out of 102 sCJD cases. A differential diagnosis of CJD was documented on the neuroradiological reports of 70 of these cases, giving a significantly improved sensitivity of 69% compared to 2012. There was no association between the location of signal change and reporting accuracy. Patients had less advanced disease compared to 2012. Conclusions: MRI reporting of sCJD by referring centres has improved, but further improvement seems possible. We re-emphasize the importance of analysing scans thoroughly for characteristic MRI patterns of sCJD to enable earlier identification of these patients. danielle: sequeira@nhs.net|ABN Bursary 26